The conspiracy - Martin, Kat (Martin, Kat. Maximum Security., 2019)
Investigating the disappearance of his best friend, Chase Garrett, the wealthy owner of Maximum Security, uncovers unscrupulous business dealings at the same time he compromises his beliefs by falling for his friend's sister.